Role of the Pro-Inflammatory Tumor Microenvironment in Extracellular Vesicle-Mediated Transfer of Therapy Resistance - Simón, Layla; Sanhueza, Sofía; Gaete-Ramírez, Belén; Varas-Godoy, Manuel; Quest, Andrew F. G. (Frontiers in Oncology, 2022)
Advances in our understanding of cancer biology have contributed to generating different treatments to improve the survival of cancer patients. However, although initially most of the therapies are effective, relapse and recurrence occur in a large percentage of these cases after the treatment, and patients then die subsequently due to the development of therapy resistance in residual cancer cells. A large spectrum of molecular and cellular mechanisms have been identified as important contributors to therapy resistance, and more recently the inflammatory tumor microenvironment (TME) has been ascribed an important function as a source of signals generated by the TME that modulate cellular processes in the tumor cells, such as to favor the acquisition of therapy resistance. Currently, extracellular vesicles (EVs) are considered one of the main means of communication between cells of the TME and have emerged as crucial modulators of cancer drug resistance. Important in this context is, also, the inflammatory TME that can be caused by several conditions, including hypoxia and following chemotherapy, among others. These inflammatory conditions modulate the release and composition of EVs within the TME, which in turn alters the responses of the tumor cells to cancer therapies. The TME has been ascribed an important function as a source of signals that modulate cellular processes in the tumor cells, such as to favor the acquisition of therapy resistance. Although generally the main cellular components considered to participate in generating a pro-inflammatory TME are from the immune system (for instance, macrophages), more recently other types of cells of the TME have also been shown to participate in this process, including adipocytes, cancer-associated fibroblasts, endothelial cells, cancer stem cells, as well as the tumor cells. In this review, we focus on summarizing available information relating to the impact of a pro-inflammatory tumor microenvironment on the release of EVs derived from both cancer cells and cells of the TME, and how these EVs contribute to resistance to cancer therapies.